2011
DOI: 10.1186/2045-3329-1-8
|View full text |Cite
|
Sign up to set email alerts
|

Liposarcoma cells with aldefluor and CD133 activity have a cancer stem cell potential

Abstract: Aldehyde dehydrogenase (ALDH) has recently been shown to be a marker of cancer stem-like cells (CSCs) across tumour types. The primary goals of this study were to investigate whether ALDH is expressed in liposarcomas, and whether CSCs can be identified in the ALDHhigh subpopulation. We have demonstrated that ALDH is indeed expressed in 10 out of 10 liposarcoma patient samples. Using a liposarcoma xenograft model, we have identified a small population of cells with an inducible stem cell potential, expressing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Stratford et al (2011) have identified candidate sarcoma CSCs in a liposarcoma cell line (SW872) after double enrichment for CD133 and ALDH High activity (ALDH High ). Cells doubly positive for CD133 and ALDH High were more clonogenic and tumorigenic when compared to parental cells or cells singly positive for either CD133 or ALDH High .…”
Section: Sarcoma Stem Cellsmentioning
confidence: 99%
“…Stratford et al (2011) have identified candidate sarcoma CSCs in a liposarcoma cell line (SW872) after double enrichment for CD133 and ALDH High activity (ALDH High ). Cells doubly positive for CD133 and ALDH High were more clonogenic and tumorigenic when compared to parental cells or cells singly positive for either CD133 or ALDH High .…”
Section: Sarcoma Stem Cellsmentioning
confidence: 99%
“…In order to effectively use ALDH1 as a CSC marker, a method known as ALDEFLUOR assay was developed to sort cells based on their ALDH1 activity 26 . Consequently, the ALDEFLUOR assay has been widely used to isolate CSC subpopulations in various tumors including different types of sarcomas 23 27 28 29 30 31 . These CSC subpopulations commonly overexpress pluripotency factors such as Sex-determining region Y-Box2 ( SOX2 ), which plays important roles in the regulation of self-renewal and tumorigenicity in CSC subpopulations of several types of cancer 32 33 34 35 36 37 .…”
mentioning
confidence: 99%
“…One of these is CD133 that has been investigated in several different cancer types, such as liposarcoma [24], glioblastoma and colorectal carcinoma [25]. In pancreatic adenocarcinoma Hermann et al [7] used CD133 in combination with CD184 to identify migratory cells essential for tumour metastasis.…”
Section: Resultsmentioning
confidence: 99%